Pengaruh Persepsi Guru Tentang Peran Kepala Sekolah Dan Motivasi Kerja Guru Terhadap Peningkatan Mutu Pendidikan Anak Usia Dini Se-Kota Bandar Lampung - Dewi Fitriani (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2022)
Quality is something that needs to be considered in the effectiveness of educational institutions. This study aims to: (1) analyze the influence of teachers' perceptions of the role of school principals on improving the quality of early childhood education in Bandar Lampung, (2) analyze the effect of work motivation on improving the quality of early childhood education in Bandar Lampung, and (3) jointly analyze the effect of teachers' perceptions on the role of school principals and work motivation with improving the quality of Early Childhood Education in Bandar Lampung.This study uses a quantitative correlation research method with a sample of 112 teachers from 157 teachers, using a questionnaire as a data collection tool, then analyzed by simple regression analysis and multiple linear regression analysis using IBM SPSS Statistic 23.The results of the study show that (1) there is an influence of teacher perceptions about the role of school principals on improving the quality of Early Childhood Education. (2) There is an effect of teacher work motivation on improving the quality of Early Childhood Education. (3) There is an influence of teachers' perceptions about the role of school principals and teacher work motivation on improving the quality of Early Childhood Education.